Developing anti-discrimination law in Europe.The 27 Member States compared - Chopin, Isabelle; Uyen Do, Thien (Luxembourg, 2011)
"The 2010 comparative review of the transposition of the EC Racial Equality and the Employment Equality Directives in the national law of 27 EU Member States is now available, with additional detailed analysis of Croatia, the Former Yugoslav Republic of Macedonia and Turkey"